Визуальное моделирование информационных параметров при анализе химико-технологических процессов - Шабанова, Ч.М.; Касимов, Р.М.; Сорокина, А.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
The paper presents the advantage of using of the visualization method for
processing of the numerical data flow, followed the processes of mathematical
description and modeling at the various stages of investigation for chemicaltechnological
processes application purposes.